Neonatal hypocalcaemia after intrauterine exposure to anticonvulsant drugs. Issue 3 (March 1977) - Friis, B; Sardemann, H
Abstract : Two cases are reported of prolonged hypocalcaemia with tetany in infants born at term, whose mothers had been treated with phenytoin and phenobarbitone in high doses. Both infants presented with jitteriness and tetany in the first and second weeks of life, and in both the hypocalcaemia was resistant to therapy over a longer period. An effect on the fetal vitamin D metabolism by phenytoin and phenobarbitone, resulting in defective bone mineralization and neonatal hypocalcaemia is suggested.